Kinesio taping® does not alter joint position sense in healthy subjects: randomized, clinical trial. - Lins, Caio Alano de Almeida; Neto, Francisco Locks; Amorim, Anita Barros Carlos de; Borges, Daniel Tezoni; Macedo, Liane de Brito; Brasileiro, Jamilson Simões (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The Kinesio Taping® is an elastic functional tape with specific characteristics that, when applied on muscles, aims to assist and functionally support them. Its effect on proprioception, a component of the somatosensory system, is still poorly understood. Objective: To assess the immediate effects of the application of Kinesio Taping® (KT) on knee joint position sense (JPS) of healthy subjects. Method: This is a controlled, randomized-blinded clinical trial. Sixty females volunteers (age: 23.3 ± 2.5 years, BMI: 22.2 ± 2.1 kg/m2) were randomly divided into 3 groups with 20 members each, and they performed one of three protocols: control - 10 minutes of resting; nonelastic adhesive tape - application over the rectus femoris (RF), vastus lateralis (VL) and vastus medialis (VM) muscles; and KT - application of KT over the same muscles. All were subjected to knee JPS evaluation on an isokinetic dynamometer, in which the analyzed variable was the absolute error, before and after interventions. Results: There were no significant changes in knee JPS in the assessed groups, using absolute error (control group p=0,14; nonelastic adhesive tape group p=0,32; KT group p=0,91). Conclusion: The application of KT on the RF, VL and VM muscles was not able to significantly improve the knee JPS of healthy women.